2015
DOI: 10.1007/s00464-015-4093-1
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of colon cancer among patients diagnosed with left colonic or sigmoid acute diverticulitis is higher than in the general population

Abstract: Colonoscopy should be continued after an initial diagnosis of left colonic or sigmoid acute diverticulitis, irrespective of the clinical or radiological presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Screening probably overestimates the prevalence of CRC in asymptomatic patients, as participation rates are usually far below 50% and symptomatic and high-risk patients probably are more likely to attend. Also, incidence rates for CRC have been used to estimate the prevalence of undiagnosed CRC in the population [55,61], which has the weakness that it is uncertain how long the CRC existed before diagnosis.…”
Section: What Are the Risk Factors For Diverticulosis Diverticulitismentioning
confidence: 99%
“…Screening probably overestimates the prevalence of CRC in asymptomatic patients, as participation rates are usually far below 50% and symptomatic and high-risk patients probably are more likely to attend. Also, incidence rates for CRC have been used to estimate the prevalence of undiagnosed CRC in the population [55,61], which has the weakness that it is uncertain how long the CRC existed before diagnosis.…”
Section: What Are the Risk Factors For Diverticulosis Diverticulitismentioning
confidence: 99%
“…Nevertheless, in a retrospective cohort study, we reported the prevalence of colorectal cancer to be 40-fold higher in patients with uncomplicated episodes than in the age-and gender-matched reference population [5].…”
Section: Dear Editormentioning
confidence: 79%
“…In a retrospective cohort study with comparison to a reference population, we reported a prevalence of CRC which was 40‐fold (standardized incidence ratio, 95 per cent c.i. 18·58 to 75·96) higher in patients with uncomplicated diverticulitis than in an age‐ and gender‐matched population.…”
mentioning
confidence: 87%